IDENTIFIKASI NILAI KARAKTER PADA ANAK USIA DINI DI PAUD CIKAL KARANGAMPEL - Latifatul Masruroh (Fakultas Agama Islam Universitas Wiralodra, 2020)
Character education is an important aspect in building nationan identity. Character can influence the development of various aspects of national life including socio-economic development. Building character is more appropriate starting at an early age, because at an early age is a golden period in the development stage, as well as being the foundation of character formation. This study focuses on the identification of value character shown by Children Age Early in early childhood Karangampel embryo. the results of the study showed that the character values ??shown by Cikal PAUD children dominated the social character values religious .